2018
DOI: 10.1093/pm/pny182
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Life Stress Emotional Awareness and Expression Interview for Women with Chronic Urogenital Pain: A Randomized Controlled Trial

Abstract: An intensive life stress emotional awareness expression interview improved physical but not psychological symptoms among women with CUP seen in a tertiary care clinic. This study suggests that targeting stress and avoided emotions and linking them to symptoms may be beneficial for this complex group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…The two trials that compared EAET (or AAET) to relaxation training, however, found equivalence of treatments-showing neither superiority nor specificity, although the smaller sample sizes limited statistical power to detect differences between EAET and another treatment [45,42]. Moreover, for most of the trials, the beneficial effects of EAET were found only in comparison to no additional treatment (i.e., waitlist control) [44,43,39] or in uncontrolled cohort trials [40,41]. Although demonstrating efficacy compared to no additional treatment is the most common evidence supporting psychological interventions for chronic pain, trials that compare EAET to better controls and comparison treatments are needed.…”
Section: Critical Analysis Of Eaetmentioning
confidence: 98%
See 3 more Smart Citations
“…The two trials that compared EAET (or AAET) to relaxation training, however, found equivalence of treatments-showing neither superiority nor specificity, although the smaller sample sizes limited statistical power to detect differences between EAET and another treatment [45,42]. Moreover, for most of the trials, the beneficial effects of EAET were found only in comparison to no additional treatment (i.e., waitlist control) [44,43,39] or in uncontrolled cohort trials [40,41]. Although demonstrating efficacy compared to no additional treatment is the most common evidence supporting psychological interventions for chronic pain, trials that compare EAET to better controls and comparison treatments are needed.…”
Section: Critical Analysis Of Eaetmentioning
confidence: 98%
“…The other trial of the life stress EAET interview was conducted in a specialty women's urology clinic among 62 women (M age = 46.0 years) who had various chronic pelvic pain conditions (e.g., interstitial cystitis, pelvic floor dysfunction, or dyspareunia) [44]. The treatment and control conditions differed at baseline on depression, which was adjusted in analyses.…”
Section: Recent Trials Of Eaetmentioning
confidence: 99%
See 2 more Smart Citations
“…EAET in its current form has been evaluated and found to be superior to treatment as usual, education controls, or even CBT in five randomized controlled trials in patients with fibromyalgia ( 17 ), irritable bowel syndrome ( 29 ), pelvic pain ( 30 ), medically unexplained symptoms ( 31 ), and musculoskeletal pain ( 18 ). Although trials of EAET have included both individual and group formats, they have all been face-to-face, and no study has been conducted through the internet.…”
Section: Introductionmentioning
confidence: 99%